Radiation in the Treatment of Oligometastatic and Oligoprogressive Disease: Rationale, Recent Data, and Research Questions. Issue 2 (March 2020) - Zayed, Sondos; Correa, Rohann J.M.; Palma, David A.
Abstract : Abstract: The use of local ablative therapy or metastasis-directed therapy is an emerging management paradigm in oligometastatic and oligoprogressive cancer. Recent randomized evidence has demonstrated that stereotactic ablative radiotherapy (SABR) targeting all metastatic deposits is tolerable and can improve progression-free and overall survival. While SABR is noninvasive, minimally toxic, and generally safe, rare grade 5 events have been reported. Given this and recognizing the often-uncertain prognosis of patients with metastatic disease, equipoise persists regarding the therapeutic window within which to deploy SABR for this indication. Ongoing phase III trials are aimed at validating the demonstrated safety, tolerability, and survival benefits while also refining patient selection, possibly with the aid of novel biomarkers. This narrative review of the role of SABR in oligometastatic and oligoprogressive disease summarizes recent randomized evidence and ongoing clinical trials, discusses our rationale for treatment and key management principles, and posits that SABR should be considered the preferred modality for multisite, metastasis-directed ablative therapy.